Хиазмы и сходные структуры в милийских текстах - Шеворошкин, Виталий (Институт языкознания РАН)
There are only two known Milyan inscriptions; both of them are written in a Lycianlike alphabet; both of them are poetic. Milyan is a late Anatolian (Hittite-Luvian) language, closely related to Lycian. The next in kin is Luvian which exists both in Cuneiform and Hieroglyphic writing. Milyan inscriptions contain many symmetric constructions, or chiasmi. A chiasmus is built in such a way that the right part of it mirrors the left part. For instance, in a Mil[yan] chiasmus prijãm-a : pasñt-e : [pixre]s-e atral-a ‘(let him glorify) the excellent detachment for Pixre’s protection’ both rhyming acc. forms, prijãm-a ... atral-a, mirror each other, being equally removed from the virtual center. On the other hand, both rhyming dat.-plur. forms [which we translate, using singular] are in the middle. Our example shows that grammatical meaning is an important feature of chiasmi. Moreover, a chiasmus is usually an autonomous unit of the text, being, in many cases, an expanded accusative direct-object construction (as our ex.) Seldom we find chiasmi which are not “autonomous”; those are beautiful structures, created to please; cf. this one: trm̃miliz : tbiplẽ : trpplẽ : tuburiz where all words start in t-, showing deep symmetrical rhymes -iz ... -iz (frame) and -ple: : -plẽ (middle); each word in the middle has 5 letters, etc. Most chiasmi have a central word (frequently a conjunction “and”). There are many long chiasmi, some showing 7 components. Somewhat similar center-symmetrical structures may be revealed on the level of inscriptions or other comparable long texts; in this case we deal with strophes as components of an inscription/text. For instance, the Milyan text on the side “c” of the inscription TL 44 (Xanthos; texts in Lycian, Greek, Milyan) has 14 strophes (I through XIV). Strophes III-IV-V in the first half of this Milyan text depict the actions of the Lycian ruler Xeriga. Accordingly, symmetrically opposed strophes X-XI-XII in the second half of the text picture the actions of another Lycian ruler, namely, Xerẽi, who was Xeriga’s successor. Xerẽi, the author of the whole inscription TL 44, has borrowed many ideas from an earlier Milyan inscription, TL 55, authored by Pixre (a de-facto ruler of the Lycian province of Phellos). Among such borrowings are several texts with chiasmi; the symmetrical structure of the Milyan text of the side “c” of TL 44 (14 strophes) was almost certainly an imitation of the structure of TL 55 which had 14 strophes.
Keywords: Языкознание